Observable effects of Ca2+ buffers on local Ca2+ signals - Solovey, Guillermo (2010)
Calcium signals participate in a large variety of physiological processes. In many instances, they involve calcium entry through inositol 1,4,5-trisphosphate (IP3) receptors (IP3Rs), which are usually organized in clusters. Recent high-resolution optical experiments by Smith & Parker have provided new information on Ca2+ release from clustered IP3Rs. In the present paper, we use the model recently introduced by Solovey & Ponce Dawson to determine how the distribution of the number of IP3Rs that become open during a localized release event may change by the presence of Ca2+ buffers, substances that react with Ca2+, altering its concentration and transport properties. We then discuss how buffer properties could be extracted from the observation of local signals. © 2010 The Royal Society.